2013
DOI: 10.2320/matertrans.m2013079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbide Size Distribution on the Impact Toughness of Tempered Martensitic Steels with Two Different Prior Austenite Grain Sizes Evaluated by Instrumented Charpy Test

Abstract: The effect of tempering temperature on the impact toughness of 0.3 mass% carbon martensitic steels with prior austenite grain (PAG) size of about 6 and 60 µm was investigated. Instrumented Charpy impact test (ICIT) was used to evaluate the impact toughness. The tempering temperature of 723 K gives the largest difference in the Charpy impact energy at room temperature between the specimens with two different PAG sizes, where the finer PAG specimen shows higher impact energy at room temperature (RT). The other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 61 publications
0
8
1
Order By: Relevance
“…The improved mechanical properties are attributed to the sub-cell structure introduced in austenite by processing HTMT and inherited martensite. In a tempered martensitic steel (0.3C -0.5Si -2Mn -0.001P -0.001S), Takebayashi et al [4] showed that refining microstructural parameters such as the prior austenite grain size improved the USE going up to 30J, but no significant effect of carbide size distribution was mentioned in this study. Im et al [5] showed that increasing molybdenum and reducing the carbon content can improve the USE, by enhancing precipitation of M 2 C-type alloy carbides instead of cementite, whose size is much lower than the critical carbide size to initiate fracture.…”
Section: Introductioncontrasting
confidence: 53%
See 2 more Smart Citations
“…The improved mechanical properties are attributed to the sub-cell structure introduced in austenite by processing HTMT and inherited martensite. In a tempered martensitic steel (0.3C -0.5Si -2Mn -0.001P -0.001S), Takebayashi et al [4] showed that refining microstructural parameters such as the prior austenite grain size improved the USE going up to 30J, but no significant effect of carbide size distribution was mentioned in this study. Im et al [5] showed that increasing molybdenum and reducing the carbon content can improve the USE, by enhancing precipitation of M 2 C-type alloy carbides instead of cementite, whose size is much lower than the critical carbide size to initiate fracture.…”
Section: Introductioncontrasting
confidence: 53%
“…In the second part of the curve, the load decreases steadily or abruptly up to the end of the test, due to crack propagation and final fracture. As reviewed in [4], the shape of this curve strongly depend on the test temperature. Abrupt load drops were attributed to brittle, unstable crack propagation, whereas ductile fracture generally induces a stable decrease in the load vs. displacement curve.…”
Section: General Behavior and Associated Fracture Mechanismsmentioning
confidence: 97%
See 1 more Smart Citation
“…This evidence is in accordance with literature results, obtained on different steels. In detail, Takebayashi et al [20] found that carbide size and distribution significantly influence impact toughness of martensitic steels.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the carbide precipitation would be the major factor in promoting TME in this study. Lee and Takebayashi reported a linear relation between the carbide size and the critical distance for cleavage crack initiation, revealing that the coarse carbides are detrimental to the impact toughness. Several researchers thought that the distribution of carbides along the martensite lath and prior austenite grain boundaries causes embrittlement of materials, promoting rapid fracture.…”
Section: Discussionmentioning
confidence: 99%